Effect of Salvia officinalis and S. sclarea on rats with a high-fat hypercaloric diet - M. A. Lieshchova; A. A. Bohomaz; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2021)
Phytotherapy for the correction of excess body weight is widely used. However, a comprehensive study of herbal preparations on the organism of model animals has been carried out only for a few plant species. Supplementing the diet of rats with closely related sage species (Salvia officinalis L. and S. sclarea L.) against the background of high-fat hypercaloric diet triggered multidirectional changes in their metabolism. The addition of crushed dry shoots of S. officinalis to the diet of animals led to a sharp increase in their body weight (up to 130.8% of the initial one in 30 days of the experiment). The body weight of the rats treated with S. sclarea for 30 days increased only up to 103.8% of their initial weight and was lower than in the control group. Addition of S. officinalis caused an increase in daily weight gain up to 253.1% of the control group, and S. sclarea – its decrease to 27.8% of the daily weight gain in the control group. In the S. officinalis group, the relative weight of the brain, spleen, and thymus decreased, while in the S. sclarea group, the relative weight of the thymus decreased and that of the colon increased. Under the influence of S. officinalis, the concentration of urea, total bilirubin, and triglycerides in the blood plasma of male rats decreased and the concentration of total protein and the activity of alkaline phosphatase increased. While consuming S. sclarea shoots, there was an increase of alkaline phosphatase activity in the rats’ blood, but atherogenic index (23.1% of the level of the control group) sharply dropped due to an increase in the concentration of high-density lipoprotein cholesterol (286.9% of the control) and a decrease in the concentration of low-density lipoprotein cholesterol (67.7% of control). In rats feeding on S. sclarea shoots, we observed a decrease in the concentration of triglycerides in the blood (39.9% of the control), a decrease in the activity of gamma-glutamyl transferase (62.8%), and an increase in the Ca/P ratio (132.5% of the control group). No significant changes were observed in CBC and WBC differential of male rats when eating S. officinalis and S. sclarea shoots. According to the results of the open field test, the physical and orientational activity of male rats under the influence of S. officinalis significantly decreased by the end of the experiment. Emotional status of rats, on the contrary, decreased when they ate dry crushed shoots of S. sclarea in the composition of the food. Thus, excess body weight of rats in the conditions of hypercaloric diet led to more pronounced deviations from the norm while consuming dry crushed shoots of S. officinalis. The addition of S. sclarea dry crushed shoots to the animals’ diet normalized the body weight in comparison with the control group, reduced the negative manifestations of obesity at the biochemical and organismal levels. In this regard, the substances that contains S. sclarea should be carefully studied for anti-atherosclerotic activity, and tea supplemented with S. sclarea shoots can be recommended as a corrective supplement in the diet of overweight people.